2022
DOI: 10.3390/ani12182464
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hematologic and Biochemical Parameters for Healthy Commercial Pigs in China

Abstract: Hematologic and biochemical data are useful for indicating disease diagnosis and growth performance in swine. However, the assessment of these parameters in healthy commercial pigs is rare in China. Thus, blood samples were collected from 107 nursery pigs and 87 sows and were analyzed for 25 hematologic and 14 biochemical variables. After the rejection of the outliers and the detection of the data distribution, the correlations between the blood parameters were analyzed and the hematologic/biochemical RIs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
4
8
0
2
Order By: Relevance
“…These observational studies have examined wide age categories, primarily middle-aged individuals, as homogenous groups without the ability to differentiate prognoses for other age classes, such as the current study's 75-year-old participants. [21,[29][30][31][32] In line with other studies, a study revealed that total and differential WBCs underwent significant alterations during childhood, particularly in the early years. Additionally, as compared to EO#, BASO#, and MONO#, LYMPH# and NEUT# showed more clear age-dependent alterations throughout childhood.…”
Section: [28]supporting
confidence: 83%
“…These observational studies have examined wide age categories, primarily middle-aged individuals, as homogenous groups without the ability to differentiate prognoses for other age classes, such as the current study's 75-year-old participants. [21,[29][30][31][32] In line with other studies, a study revealed that total and differential WBCs underwent significant alterations during childhood, particularly in the early years. Additionally, as compared to EO#, BASO#, and MONO#, LYMPH# and NEUT# showed more clear age-dependent alterations throughout childhood.…”
Section: [28]supporting
confidence: 83%
“…Thromboxane B2 levels, a known marker of CARPA, were comparable to baseline levels in siPLG- and PBS-treated swine at 5 h ( Figure 3 A). To monitor for potential signs of inflammation, white blood cell (WBC) count was analyzed, and levels were within a normal range 34 and comparable to untreated swine ( Figure 3 B). Untreated swine underwent anesthesia but did not receive any further injections; this control group was included in specific analyses when blood samples in the PBS group were not available.…”
Section: Resultsmentioning
confidence: 99%
“…PCV2 affects the functioning of organs and systems, leading to morphological and biochemical changes in the blood composition (Rajesh et al, 2020). Meanwhile, the biochemical profile of animals in the industrial herd is utilized to monitor the health status of widely used animals, assessing pig herds for the presence of diseases, predicting their productivity, or evaluating feeding practices (Yefimov et al, 2017;Zhang et al, 2022;Dimitrakakis et al, 2022). However, the assessment of these parameters in healthy industrial pigs is seldom encountered.…”
Section: біохімічні показники сироватки крові у відгодівельних свиней...mentioning
confidence: 99%